PERANAN ULAMA BANJAR ABAD KE-20 DALAM TRADISI PENULISAN HADIS ARBAâÄªN DI BANJAR DAN MALAYSIA - Said Iderus, Muhammad Hasan (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2016)
Banjar is famous for its great scholars and have an important role in the Islamic world. In this study, Banjarese scholars had passions and purposes to enhance, strengthen and develop the tradition of writingHadith. The books of hadith they wrote is not only applicable in Islamic boarding school but also for public usage in this country as well as other countries.Banjarese scholars who was related to hadith ArbaCin the 20th century were Kasyful Muhammad Anwar, Anang Syacrani Arif, Muhammad Syukeri Unus, and Ahmad Fahmi Zamzam. This study attempts to explain the background of those scholars and their roles in the scientific tradition of Hadith in Banjar as an effort to introduce the Islamic scholars in Nusantara to Islamic world. This research is based on analysis of historical and biographical data obtained from the collection of documentsand processed descriptively. The study found that the role of Banjarese scholars in the 20th century gave a new nuance to the study of hadith in Banjar and Malaysia.